Prognostic Value and Risk Factors of Treatment-Related Lymphopenia in Malignant Glioma Patients Treated With Chemoradiotherapy: A Systematic Review and Meta-Analysis - Zhang, Yongchao; Chen, Shichao; Chen, Hualei; Chen, Shanshan; Li, Zhen; Feng, Enshan; Li, Wei (Frontiers in Neurology, 2022)
Background: Immunotherapy has shown promising therapeutic efficacy in various cancers but not gliomas. Circulating lymphocytes play critical roles in cancer control and responses to immune checkpoint inhibitors. Treatment-related lymphopenia has been associated with poor survival in patients with various tumors. This meta-analysis evaluated the risk and impact of lymphopenia in patients with glioma. Methods: The PubMed, Embase, Web of Science, and Cochrane Library databases were comprehensively searched. Eligible studies were included if they reported the incidence and risk factors of lymphopenia and the impact of lymphopenia on survival. Stata 16.0 was used for this meta-analysis. Results: A total of 21 studies were included in the final systematic review and 20 were included in the quantitative analysis. The overall incidence of grade III/IV lymphopenia was 31.6% [95% confidence interval (CI), 22.3–40.8%]. Pooled results based on pathology of glioma revealed that the incidence in astrocytoma and astrocytoma oligodendroglioma patients was 20.2% (95% CI:5.9–34.4%), and the incidence in glioblastoma patients was 27.6% (95% CI:16.2–38.9%). Lymphopenia was associated with poor overall survival (hazard ratio, 1.99; 95% CI, 1.74–2.27; P< 0.001) compared to no lymphopenia. Brain receiving radiation dose of 20 or 25 Gy, female sex, older age, lower baseline lymphocyte count, and dexamethasone dose > 2 mg instead of baseline use were risk factors for lymphopenia. Conclusions: Treatment-related lymphopenia was associated with decreased survival in patients with glioma. Optimization of chemoradiation regimens, particularly in patients with concurrent risk factors, can reduce lymphopenia and potentially improve survival in the era of immunotherapy.